"You'll See": Younger Women Interviewing Older Women in Qualitative Research. Issue 8 (16th November 2020) - Jen, Sarah; Zhou, Yuanjin; Jeong, Mijin
ABSTRACT: Understanding the co-construction of the interview process between older adult research participants and relatively younger interviewers requires a nuanced analysis of positioning, reflexivity, and power within interviewing dynamics, accounting for differences in historical context and lived experience. Guided by a feminist life span approach, this study examined interviewing dynamics between a younger woman interviewer and older women research participants, ages 57–93 (mean = 65.3), in two qualitative studies completed five years apart. Four themes emerged: 1) contrasting experiences drew explicit attention to discrepancies in historical context, age, and life experience between participants and the interviewer. Similarities often arose in the theme of 2) invoking expertise in which participants oriented to or invoked their own expertise in their life story and experiences and the interviewer's expertise in research, sexuality studies, and social services. Participants enacted 3) demonstrating care, by prioritizing the researcher's goals, offering advice, and expressing hopes for younger generations. Finally, 4) the participants and researcher used distinctive conversational strategies when addressing challenging or sensitive topics. This paper contributes a needed analysis of age-related dynamics in qualitative research as well as indicating potential strategies to inform reflexive cross-generational conversations in gerontological research and practice more broadly.